Neuro-Cardio Mechanisms in Huntington’s Disease and Other Neurodegenerative Disorders - Critchley, Bethan J.; Isalan, Mark; Mielcarek, Michal (Frontiers in Physiology, 2018)
Although Huntington’s disease is generally considered to be a neurological disorder, there is mounting evidence that heart malfunction plays an important role in disease progression. This is perhaps not unexpected since both cardiovascular and nervous systems are strongly connected — both developmentally and subsequently in health and disease. This connection occurs through a system of central and peripheral neurons that control cardiovascular performance, while in return the cardiovascular system works as a sensor for the nervous system to react to physiological events. Hence, given their permanent interconnectivity, any pathological events occurring in one system might affect the second. In addition, some pathological signals from Huntington’s disease might occur simultaneously in both the cardiovascular and nervous systems, since mutant Huntingtin protein is expressed in both. Here we aim to review the source of HD-related cardiomyopathy in the light of recently-published studies, and to identify similarities between HD-related cardiomyopathy and other neuro-cardio disorders.